Acute depletion of diacylglycerol from the Cis-Golgi affects localised nuclear envelope morphology during mitosis - Chung, Gary Hong Chun; Domart, Marie-Charlotte; Peddie, Christopher; Mantell, Judith; Mclaverty, Kieran; Arabiotorre, Angela; Hodgson, Lorna; Byrne, Richard D.; Verkade, Paul; Arkill, Kenton P.; Collinson, Lucy M.; Larijani, Banafshé (American Society for Biochemistry and Molecular Biology, 2018)
Dysregulation of nuclear envelope (NE) assembly results in various cancers; for example, renal and some lung carcinomas ensue due to NE malformation. The NE is a dynamic membrane compartment and its completion during mitosis, is a highly regulated process but the detailed mechanism still remains incompletely understood. Previous studies have found isolated diacylglycerol (DAG) containing vesicles are essential for completing the fusion of NE in non-somatic cells. We investigated the impact of DAG depletion from cis-Golgi in mammalian cells on NE reassembly. Using advanced electron microscopy, we observed an enriched DAG population of vesicles at the vicinity of the NE gaps of telophase mammalian cells. We applied a miniSOG-C1-domain tag that localized DAG-enriched vesicles at the perinuclear region, which suggested the existence of NE fusogenic vesicles. We quantified the impact of Golgi-DAG depletion by measuring the in situ NE rim curvature of the re-forming NE. The rim curvature in these cells was significantly reduced compared with controls, which indicated a localized defect in NE morphology. Our novel results demonstrate the significance of the role of DAG from cis-Golgi for the regulation of NE assembly.